Strategi Peningkatan Kemampuan Numerasi Siswa Di SDN Wonocolo 1 Taman Sidoarjo Melalui Program Kampus Mengajar - Irawati, Sofi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
Improving students' numeracy skills is the most important thing to improve. This is one of the elements in creating superior resources as well as the strength of the education system, especially in Indonesia. This can be proven at SDN Wonocolo 1 Taman Sidoarjo where this school is said to be lacking in students' numeracy skills. Because many students have a low average score in their numeracy, especially in grade 5, namely 5A and 5B. can be proven by the implementation of AKM where the average value obtained in the numeration is very low. Therefore a strategy or program is needed that can be used to improve the numeracy skills of students at SDN Wonocolo 1 Taman Sidoarjo. The method used is descriptive qualitative method using data collection techniques namely by interviews, documentation and observation.